Arctic charr (Salvelinus alpinus) in Windermere (Cumbria) - Baroudy, Ellyscar (1995)
The Arctic charr of the British Isles are all non-migratory and are near their most southernmost range. Windermere is one of the few lowland lakes at southerly latitudes to contain a substantial proportion of Arctic charr. The first recorded mention of charr in Windermere was made around 1540 but it was not till the 17th century that different "sons" of charr were recognized, based on differences in their breeding behaviour. In the 1960's, the presence of two distinct populations, autumn spawners and spring spawners were discovered. In the 1980's it was shown that there were at least four races of charr in Windermere, based on genetic characteristics. Recently, the lake has changed due to inputs of phosphorus from treated sewage released into the lake resulting in eutrophication particularly in the south basin. Since the mid-1980's the numbers of charr caught in the south basin have declined.